2016
DOI: 10.1371/journal.pone.0158117
|View full text |Cite
|
Sign up to set email alerts
|

Food for Pollinators: Quantifying the Nectar and Pollen Resources of Urban Flower Meadows

Abstract: Planted meadows are increasingly used to improve the biodiversity and aesthetic amenity value of urban areas. Although many ‘pollinator-friendly’ seed mixes are available, the floral resources these provide to flower-visiting insects, and how these change through time, are largely unknown. Such data are necessary to compare the resources provided by alternative meadow seed mixes to each other and to other flowering habitats. We used quantitative surveys of over 2 million flowers to estimate the nectar and poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
280
3
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 277 publications
(306 citation statements)
references
References 122 publications
15
280
3
8
Order By: Relevance
“…Anyway, the 'native only' policies in landscaping plantings have to be always contextualized, because there are exceptions where nonnative species may play an important role (Kendle and Rose, 2000). In this regard, recent studies have found that using plants from one region of origin may not be the optimal strategy for providing resources for pollinators in an urban context (Hicks et al, 2016;Salisbury et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Anyway, the 'native only' policies in landscaping plantings have to be always contextualized, because there are exceptions where nonnative species may play an important role (Kendle and Rose, 2000). In this regard, recent studies have found that using plants from one region of origin may not be the optimal strategy for providing resources for pollinators in an urban context (Hicks et al, 2016;Salisbury et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In natural circumstances, plant-pollinator interactions may rapidly change at the spatio-temporal scale (Kubo et al 2008;Fründ et al 2011;Bagella et al 2013), and food resources can be highly aggregated in space or time (Elzinga et al 1998;Hatfield & Lebuhn 2007). Floral food resource quality, quantity and production rates show a huge variation with plant species, time of the day, age of flowers and competitors' consumption (Galetto & Bernardello 2004;Nicolson et al 2007;Hicks et al 2016). The number of floral resource species, quantity and density of flowers and the amount of food in flowers at least partly determine pollinator abundance, diversity and resource-visit frequency, and are the strongest factors structuring pollinator communities (Potts et al 2004;Iserbyt et al 2008;Dennis 2010;Curtis et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Given the abundance and diversity of floral and nesting resources present in urban and suburban gardens [77,78], it is possible that many bees do not forage beyond garden boundaries, in which case, ecosystem service flow to adjacent agricultural sites would be negligible. Indeed, mark-recapture experiments on bees from urban gardens failed to document bee movement between gardens in New York City, even though bees were anecdotally observed leaving gardens after a foraging bout [41].…”
Section: Discussionmentioning
confidence: 99%